ANALISIS KAIDAH AL-IJTIHAD LA YUNQADH BI AL-IJTIHAD DAN APLIKASINYA DALAM HUKUM ISLAM - Muhammad Rusdi bin Muhammaddiah (Hukum Keluarga Islam IAIN LANGSA, 2019)
The principle of al-Ijtihad la Yunqadh bi al-Ijtihad is a rule of kulliyah aghlabiyah(mayoritative-representative) in the study of Usul Jurisprudence. In the construction of Islamiclaw itself, ijtihad is an important media which plays a very large role. Without ijtihad, of courseIslamic scholarship will be poor and arid in responding to various problems in accordance withthe time and place. The problem that then arises from the open door of ijtihad is, when an ijtihadhas gained legitimacy, whether the legal product from the results of ijtihad can be canceled andannulled simply by other ijtihad results. This becomes interesting and important especially withsomething related to legal certainty. A comprehensive discussion of these rules will provide acomplete picture and then contextualized in various legal practices in Indonesia, especiallyIslamic legal practices in order to produce legal certainty in an issue.